2012
DOI: 10.2174/1874364101206010036
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of Electrogenic Sodium Bicarbonate Cotransporter NBCe1 in Ocular Tissues

Abstract: Electrogenic Na+-HCO3- cotransporter NBCe1 is expressed in several tissues such as kidney, eye, and brain, where it may mediate distinct biological processes. In particular, NBCe1 in renal proximal tubules is essential for the regulation of systemic acid/base balance. On the other hand, NBCe1 in eye may be indispensable for the maintenance of tissue homeostasis. Consistent with this view, homozygous mutations in NBCe1 cause severe proximal renal tubular acidosis associated with ocular abnormalities such as ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In one case, a 12-yr-old girl with a defect only in (renal) NBCe1-A variant did not have band keratopathy (412), consistent with variable penetrance or with the hypothesis that it is specifically a defect in NBCe1-B and -C in the corneal endothelium that causes the band keratopathy. If HCO 3 Ϫ secretion across the corneal endothelium and into the aqueous humor were compromised, a localized elevation of [HCO 3 Ϫ ] in the subepithelial region of the corneal stroma might be expected to enhance the deposition of Ca 2ϩ salts (928,989). Band keratopathy is not a feature associated with pRTA in individuals with the Q29X or R881C mutations (TABLE 6).…”
Section: I) Central Nervous System A) Mental Retardation Migraine mentioning
confidence: 99%
“…In one case, a 12-yr-old girl with a defect only in (renal) NBCe1-A variant did not have band keratopathy (412), consistent with variable penetrance or with the hypothesis that it is specifically a defect in NBCe1-B and -C in the corneal endothelium that causes the band keratopathy. If HCO 3 Ϫ secretion across the corneal endothelium and into the aqueous humor were compromised, a localized elevation of [HCO 3 Ϫ ] in the subepithelial region of the corneal stroma might be expected to enhance the deposition of Ca 2ϩ salts (928,989). Band keratopathy is not a feature associated with pRTA in individuals with the Q29X or R881C mutations (TABLE 6).…”
Section: I) Central Nervous System A) Mental Retardation Migraine mentioning
confidence: 99%
“…pRTA patients with homozygous NBCe1 mutations invariably presented with ocular abnormalities, typically consisting of band keratopathy, glaucoma, and cataract, indicating that the normal transport activity of NBCe1 in eye is indispensable for the maintenance of tissue homeostasis (Suzuki et al, 2012). …”
Section: Ocular Phenotypes Caused By Nbce1 Mutationsmentioning
confidence: 99%
“…It is well-known that the trabecular meshwork is the main site regulating aqueous outflow in the human eye (Bill, 1975). Accordingly, it is tempting to speculate that the inactivation of NBCe1 in trabecular meshwork cells may be responsible for the occurrence of high-tension glaucoma usually observed in the pRTA patients with homozygous NBCe1 mutations (Suzuki et al, 2010, 2012). Interestingly, the pRTA patient carrying the homozygous Q29X mutation also presented with bilateral high-tension glaucoma (Igarashi et al, 2001).…”
Section: Ocular Phenotypes Caused By Nbce1 Mutationsmentioning
confidence: 99%
“…This mutation is separate among others found in the transmembrane domain (TMD) [7, 10]. The effect of the R298S mutation remains controversial in the literature.…”
Section: Introductionmentioning
confidence: 95%
“…Prior studies have demonstrated that NBCe1 variants also play a key role in maintaining ocular pressure and corneal clarity. NBCe1 defects in ocular tissue have been associated with glaucoma, band keratopathy (calcium deposition along the stroma), and cataracts [10, 11]. Additionally, NBCe1 variants participate in pH regulation of extracellular brain space, and are thought to modulate neuronal excitability in astrocytes by regulating local pH [12, 13].…”
Section: Introductionmentioning
confidence: 99%